An Analysis of Non-Observance the Maxim in " Knives Out " Movie script - Tamrin - Tamrin; Muarifuddin Muarifuddin; Arman Arman (ELITE: Journal of English Language and Literature, 2022)
This research is a pragmatic approach study of an analysis of Non-Observance the Maxim in Knives Out Movie Script. The objectives of this researcher are to find out the types of Non-Observance a Maim in Movie scripts and to find out the dominant types of Non-Observance used by all the character’s utterances. The researcher used the content analysis qualitative method to describe and analyze the selected of Non-Observance which are watching movies and then classifies them according to Paul Grice’s concept types of Non-Observance. The researcher used content analysis which focuses on classifying the types of Non-Observance and the dominant types of Non-Observance in Knives Out movie carried out by all the characters. The researcher found that the characters use all types of Non-Observance. The first flounting there are Quality (3), Quantity (8), Relation (1) Manner (-). Second is Violation, they are Quality (4), Quantity (3), Relation (1), and Manner (-). Third, is Opting Out, they are {Quality (-) Quantity (1) Relation (1) Manner (-), Forth is Infringing, they are Linguistics Performance (-), Culture Impairment (-) Cognitive Impairment (1), and the last is Suspending (1) Based on the data above, it reveals that all characters in their utterances dominantly used the Non-Observance of Flounting with 13 data.